Selected aspects of fungal infections in hospitals - Siczyńska, Bożena; Dyk, Danuta (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2013)
In the last few years, a doubling of the number of hospital fungal infections in hospitalized patients has been observed. These infections account for about 9-10% of all hospital infections and may affect skin, mucous membranes, organs and entire systems. They are the result of an interaction between microbes, the patient’s immunity level and mode of disease transmission. This study presents the epidemiological situation in hospital fungus infections and discusses the current methods for diagnosing, treating and preventing systemic mycoses.